PSXII-18 Treatment of composted poultry litter with natural hop extracts, effects on nitrogen accumulations, coliforms and select Gram-positive pathogenic and antimicrobial resistant bacteria. (30th November 2020) - Castillo-Castillo, Yamicela; Anderson, Robin; Hume, Michael; Flythe, Michael; Nisbet, David; Arzola-Alvarez, Claudio; Castillo, Francisco; Salinas-Chavira, Jaime; Ontiveros, Marina; Copado, Ramon; Ruiz-Barrera, Oscar
Abstract: Poultry litter, produced by intensive poultry production systems, is a potentially valuable crude protein feedstuff for ruminants if effectively treated to kill pathogens before feeding. Composting effectively kills pathogens but risks losses of ammonia during uric acid degradation. To test if hop extracts may help preserve uric acid concentrations during composting, 11-g portions of used wood chip litter (WCL, 88% dry matter) were treated with 6 mL water containing Galena or Chinook hop extracts to achieve 0.06 g of either extract/g WCL. Control WCL was treated with buffer alone. The WCL was distributed to 50-mL tubes (3 tubes/treatment), capped and incubated in Gas Pac jars for 8 days at 30 o C, followed by 3 days at 37 o C and an additional 2 days at 42 o C to simulate a 13-day compost period. A repeated measures analysis of variance revealed a treatment by day interaction on uric acid (P < 0.05), with concentrations being highest upon initiation of composting (41.9 ± 3.6 µmol/g), lowest on day 13 for the untreated compost (17.5 ± 9.2 µmol/g) and intermediate for Galena and Chinook hop-treated compost (28.0 ± 4.7 and 25.8 ± 0.8 µmol/g, respectively). Effects of treatment, day of composting or their interaction, however, were not observed (P > 0.05) on concentrations of ammonia and urea, which averaged 1.2 ± 1.0 and 2.9 ± 0.6 µmol/g, respectively. As expected, an effect of day-of composting on survivability (P < 0.05) of select bacterial populations was confirmed, with counts being decreased more than 3.0 log10 units after 13 days composting than on day 0 for enterococci, staphylococci, lactic acid bacteria, coliforms and total aerobes (6.7 ± 0.09, 9.0 ± 0.01, 5.8 ± 0.16, 5.9 ± 0.09 and 9, 9 ± 0.06 log10 CFU/g, respectively). These results indicate that hops-treatment may help preserve crude protein within WCL during composting.